Palafox Mendoza, J. (MDCCLXII). Breve Tratado de escribir bien y de la perfecta Ortografía. Madrid: Imprenta de Don Gabriel Ramírez. - María Aránzazu Bartolomé Tutor (Universidad Complutense de Madrid, 2002)
Sin resumen